Analysis of Food Insecurity and Surveillance Based on the FANP Method in the northwest of Iran - Helda Tutunchi; Alireza Ostadrahimi; Soltanali Mahboob; Sirous J Tabrizi (Journal of Applied Sciences and Environmental Management)
Food insecurity is frequent in both developed and developing countries, affecting from 5% to 25% of the general population. It has considerable health impacts on the physical, social, and psychological status of individuals in communities suffering from food insecurity. In this paper, we seek to use the Fuzzy analytical network process (FANP) for analysis of food insecurity surveillance and selecting the best strategies for improving it. This cross-sectional study was conductedon 300 subjects (132 male and 168 female) selected randomly in the Asadabadi area of the northwest of Iran.The method is validated using the structural validation approach. @JASEM